Evaluation of the distribution and mobility of labile phosphorus in sediment profiles of Lake Nansi, the largest eutrophic freshwater lake in northern China. (February 2023) - Zheng, Ye; Sun, Yu; Zhang, Zhihong; Han, Chao; Wang, Zhaode; Liu, Cheng; Ke, Fan; Zhang, Lei; Shen, Qiushi
Abstract: Understanding various biogeochemical processes, especially in eutrophic sediments, necessitates fine-scale phosphorus (P) measurements in pore waters. To the best of our knowledge, the fine-scale distributions of P across the sediment profiles of Lake Nansi have rarely been investigated. Herein we evaluated the dynamic distributions of labile P and Fe across the sediment-water interface (SWI) of Lake Nansi at two-dimensional (2D) and sub-millimeter resolution, using well-established colorimetric diffusive gradients in thin films (DGT) methodology. The concentrations of labile P in all investigated sediment profiles exhibited strong spatial variations, ranging from 0 to 1.50 mg/L with a considerable number of hotspots. Lake Nanyang (0.55 ± 0.21 mg/L) had the highest mean concentration of labile P, followed by Lake Dushan (0.38 ± 0.19 mg/L), Lake Weishan (0.28 ± 0.21 mg/L), and Lake Zhaoyang (0.18 ± 0.09 mg/L). The highest concentrations of labile P were always detected in Lake Dushan, which had been subjected to excessive exogenous P pollution. The co-distributions of labile P and Fe in the majority of the sediment of Lake Nansi confirmed highly positive correlations ( P  < 0.01), suggesting that the mobility of labile P throughout the SWI was likely governed by iron redox processes. The apparent diffusion fluxes of P across the SWI ranged from −7.7 to 33.6 μg/m 2 ·d, with a mean value of 5.26 ± 7.80 μg/m 2 ·d. Positive apparent fluxes for labile P were recorded in most sediment cores, demonstrating the strong upward mobility of P from the sediment to the overlying water. Our results provided accurate and extensive information regarding the micro-distribution and dynamic exchange of labile P across the SWI. This allows for a better understanding of eutrophication processes and the implementation of P management strategies in Lake Nansi. Graphical abstract: Image 1 Highlights: The spatial variation and mobility of P in Lake Nansi were characterized using DGT. 2D, heterogeneously micro-distribution of P in the sediment profile was observed. Labile P had a northward and downward spatial gradient, related to human activity. The mobility of P across the SWI was likely governed by iron redox processes. Fine-scale measurement improves the accuracy P-cycle depiction for eutrophic lake.